2021
DOI: 10.3390/s21093003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pilots’ Fatigue Status Based on Electrocardiogram Signals

Abstract: Fatigue is an important factor affecting modern flight safety. It can easily lead to a decline in pilots’ operational ability, misjudgments, and flight illusions. Moreover, it can even trigger serious flight accidents. In this paper, a wearable wireless physiological device was used to obtain pilots’ electrocardiogram (ECG) data in a simulated flight experiment, and 1440 effective samples were determined. The Friedman test was adopted to select the characteristic indexes that reflect the fatigue state of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Karthikeyan et al employed a 1-h visuo-spatial 2-back task to study the effects of anodal transcranial direct current stimulation on working memory under fatigue ( Karthikeyan et al, 2021 ). Additionally, a 60 min Stoop color-word task ( Nikooharf Salehi et al, 2022 ) and a flight simulator task ( Pan et al, 2021 ) were used to induce a mental state of fatigue. While these models may be suitable for scenarios involving static operators, they might not be applicable to actual dynamic settings, such as those encountered by pilots, firefighters and first responders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karthikeyan et al employed a 1-h visuo-spatial 2-back task to study the effects of anodal transcranial direct current stimulation on working memory under fatigue ( Karthikeyan et al, 2021 ). Additionally, a 60 min Stoop color-word task ( Nikooharf Salehi et al, 2022 ) and a flight simulator task ( Pan et al, 2021 ) were used to induce a mental state of fatigue. While these models may be suitable for scenarios involving static operators, they might not be applicable to actual dynamic settings, such as those encountered by pilots, firefighters and first responders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated a correlation between ECG signals and psychomotor vigilance task (PVT) performance, as well as the effectiveness of HRV indices in assessing cognitive task-related errors. Leveraging sensitive features extracted from ECG, algorithms like learning vector quantization and random forest tree classifiers achieve impressive accuracy in identifying fatigue states, underscoring HRV as a potential indicator for evaluating worker fatigue ( Chua et al, 2012 ; Zhao et al, 2012 ; Pan et al, 2021 ; Xu et al, 2021 ; Takada et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…HE ongoing evolution of the aviation industry hinges on maintaining rigorous safety standards, as advancements in aircraft design, endurance, and safety have contributed to a worldwide decrease in aircraft accidents [1,2]. Cognitive tendencies, particularly those related to attentional focus, are common among pilots and can be elicited by various factors such as cockpit alerts, extreme weather turbulence, takeoff, and landing.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning techniques are widely used for classification and prediction problems in diverse fields [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] as well as welding monitoring and discontinuity detection. In a research conducted by Chen et al [ 33 ] artificial neural network (ANN) and support vector machine (SVM) were employed to classify welding defects using emission spectrum data.…”
Section: Introductionmentioning
confidence: 99%